2017
DOI: 10.1186/s12971-017-0111-5
|View full text |Cite
|
Sign up to set email alerts
|

Determining non-cigarette tobacco, alcohol, and substance use typologies across menthol and non-menthol smokers using latent class analysis

Abstract: BackgroundSubstance use and mental health are robustly associated with smoking and poor cessation outcomes, but not often examined in combination with menthol cigarette smoking, which is also associated with lower quit rates. This study identified classes of Black and White menthol and non-menthol cigarette smokers based on demographics, alcohol, drug, and other tobacco use behaviors.MethodsUsing screening data from two studies, latent class analysis (LCA) was conducted to classify n = 1177 menthol and non-men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Menthol cigarette use, compared to nonmenthol cigarette use, was associated with NH Black and Hispanic race/ethnicity, female gender, and greater interest in quitting smoking during SUD treatment. Two U.S. studies reported that menthol use was not associated with past 30-day alcohol use (Rath et al, 2016; Villanti et al, 2018) while another U.S. study of smokers from the community found no relationship between menthol use and binge drinking, frequency of consuming alcohol, or number of drinks per drinking occasion (Cohn et al, 2017). It is not clear at this time whether menthol plays a role in the disparities of smoking among persons with and without AUD.…”
Section: Discussionmentioning
confidence: 99%
“…Menthol cigarette use, compared to nonmenthol cigarette use, was associated with NH Black and Hispanic race/ethnicity, female gender, and greater interest in quitting smoking during SUD treatment. Two U.S. studies reported that menthol use was not associated with past 30-day alcohol use (Rath et al, 2016; Villanti et al, 2018) while another U.S. study of smokers from the community found no relationship between menthol use and binge drinking, frequency of consuming alcohol, or number of drinks per drinking occasion (Cohn et al, 2017). It is not clear at this time whether menthol plays a role in the disparities of smoking among persons with and without AUD.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, compared with previous studies on smoker typologies in general smokers who did not seek help to quit smoking ( Cohn et al, 2017 ; Furberg et al, 2005 ; Manley et al, 2009 ; Timberlake, 2008 ) or in smokers participated in studies on face-to-face smoking cessation interventions ( Batra et al, 2008 ; Del Río et al, 2011 ), we used a different sample and included a broader range of participant characteristics to identify subtypes of smokers, which limited the comparability. However, when comparing some individual features between our smoker typology and other multi-dimensional smoker typologies identified in these previous studies, we still found some similarities.…”
Section: Discussionmentioning
confidence: 99%
“…However, when comparing some individual features between our smoker typology and other multi-dimensional smoker typologies identified in these previous studies, we still found some similarities. For example, Batra et al (2008) found a typology characterized by low levels of tobacco dependence and craving, and high levels of sensation seeking; Cohn et al (2017) found a “poly-substance users” typology characterized by young, higly educated, and light-to-moderate smokers; and Furberg et al (2005) found a typology of extrovert personality traits and light smoking. Our Cluster 1 seems to be consistent with these subtypes of smokers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,25 Alcohol, marijuana, and other drug use were assessed as wavespecific variables (not based on study entry assessment) and included as covariates because substance use is robustly associated with cigarette smoking in general, and prevalent among young adult menthol smokers. 27,28 Current alcohol use was assessed differently for waves 5 and 6 versus waves 7 and 8. In waves 5 and 6, all participants were asked about the frequency of their current use, with response options "every day," "some days," and "not at all."…”
Section: Measures Past 30-day Cigarette Smoking and Subjective Responmentioning
confidence: 99%